Analisis Kebijakan Populis dan Peta Mutu Pendidikan di Provinsi Kepulauan Bangka Belitung - Gustin Gustin (Lembaga Penjaminan Mutu, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2019)
The government continues to improve the education sector with various steps, one of which is by making regular curriculum improvements, such as the change from the level of education to the 2013 curriculum. Changes in the curriculum to 2013 curriculum, among others, to meet the golden generation of Indonesia. If changes are made, it is hoped that the young generation in the future will be able to realize the ideals of Indonesian education. with the low quality of education of the population, it will also affect the low competitiveness of the workforce of the Bangka Belitung Islands Province in the labor market both the labor market in this area itself and the labor market outside the region. Related to the education quality map in the province of Kep. Bangka Belitung as Strengthening HR to be able to oversee the implementation of PMP is still very much needed, especially for the development of the capacity of local facilitators to improve the quality of the learning process. Mapping the quality of education must be maintained in order to improve the quality of schools from time to time.Keywords: Populist, Quality, Education Abstrak Pemerintah secara terus-menerus membenahi sektor pendidikan dengan berbagai langkah, salah satunya adalah dengan melakukan perbaikan kurikulum secara berkala, seperti perubahan dari kurikulum tingkat satuan pendidikan menjadi kurikulum 2013. Perubahan kurikulum menjadi kurikulum 2013, antara lain dimaksudkan untuk menyongsong generasi emas Indonesia. Jika perubahan kurikulum ini dilakukan, maka diharapkan generasi muda di masa depan akan dapat mewujudkan cita-cita pendidikan bangsa Indonesia. dengan kualitas pendidikan penduduk yang rendah, akan menyebabkan juga rendahnya daya saing tenaga kerja Provinsi Kepulauan Bangka Belitung dalam pasar kerja baik pasar kerja di daerah ini sendiri maupun pasar kerja di luar daerah. Terkait Peta Mutu pendidikan di Provinsi Kep. Bangka Belitung bahwa Penguatan SDM untuk dapat mengawal implementasi PMP masih sangat dibutuhkan, terutama untuk pengembangan kemampuan fasilitator daerah untuk meningkatkan mutu proses pembelajaran. Pemetaan mutu pendidikan harus dijaga kontinuitasnya sehingga dapat dipelajari perubahan mutu sekolah dari waktu ke waktu.